Does mesofaunal abundance and composition influence mangrove leaf litter decomposition? - Loría-Naranjo, Margarita (2025)
Introduction: Litter decomposition in mangrove forest is a process in which organic matter produced as leaves in the trees is later transferred to the sediment. Several invertebrates participate in the fragmentation of leaves, and they might have a great impact in the later stages of decomposition of mangrove leaves. Objective: The study aims to characterize mesofauna inhabiting leaf litter of Rhizophora racemosa, in the South Pacific of Costa Rica during the dry and rainy season. Methods: Five pre-weighted litter bag samples were set out during each season. Each sample consisted of specimens adhered to the leaves after 0, 15, 30, 60, 90 and 120 days, from two sites in Térraba-Sierpe National Wetland. The samples were washed in a sieve (0.5 mm) and the organisms were separated and identified. Taxa were assigned to trophic groups to evaluate their influence in the decomposition of the leaves. Additionally, leaf detritus samples retained in the sieve were dried in an oven at 70 °C to calculate the remaining vegetal matter for each site and season. Results: The most abundant taxa were: Bivalvia (26 %), Nematoda (19.45 %), Gastropoda (14.78 %), Nemertea (14.61 %), and Ostracoda (8.20 %). Based on the trophic classification of the mesofauna found, it is expected that most of them are indirect consumers of R. racemosa litter. Correlation analysis shows that, depending on the site and the season, the mass loss of leaf litter was greater with a greater mesofauna abundance. A combined influence of water salinity, temperature and dissolved oxygen explains 25 % of the changes observed in the mesofauna found in leaf litter samples throughout the sampling period. Conclusions: Leaf litter decomposition process evidences the presence of an abundant and diverse mesofauna community. The abundance of this mesofauna seems to have a positive influence on the decomposition of the leaves. It is a vital issue to comprehend the role of mesofauna as potential consumers of mangrove leaf litter, in order to conservate biodiversity in this ecosystem.